What determines banking company stock returns? Empirical evidence from Indonesia stock exchange - Indupurnahayu,; Shanti Lysandra,; Evin Sofianti,; Renea Shinta Aminda,; Abrista Devi, (Technium Business and Management, 2022)
The purpose of this study was to investigate the determinants of stock returns of banking companies listed on the Indonesia Stock Exchange (IDX). The panel econometric approach was used to analyze panel data obtained from 31 banking companies listed in the 2018-2019 period. The research findings show that profitability has a significant effect on stock returns. Net Profit Margin has a positive effect on stock returns, while Return on Equity has a negative effect. Meanwhile, the size and leverage of the company have no significant effect on stock returns.